Experimental study of a physician‐controlled electrocautery‐enhanced delivery system incorporating a newly developed lumen‐apposing metal stent for interventional endoscopic ultrasound (with videos). (25th January 2022) - Mukai, Shuntaro; Itoi, Takao; Tsuchiya, Takayoshi; Ishii, Kentaro; Tanaka, Reina; Tonozuka, Ryosuke; Furuichi, Yoshihiro; Joyama, Eri; Miyazawa, Hideaki; Sofuni, Atsushi
Abstract: Background/Purpose: Although the lumen‐apposing metal stent (LAMS) is useful for interventional endoscopic ultrasound (EUS) procedures, there has been some concern about the potential for stent‐induced adverse events because of the high lumen‐apposing force. A newly designed LAMS with less lumen‐apposing force has been developed for use with a physician‐controlled electrocautery‐enhanced delivery system. The aim of this animal study was to evaluate the feasibility of performing interventional EUS using this newly designed LAMS system. Methods: Endoscopic ultrasound‐guided cystogastrostomy was performed using the novel LAMS three times in a wet simulation model. EUS‐guided gastroenterostomy and EUS‐guided gallbladder drainage were then performed using the system in four pigs. Results: The LAMS was successfully placed in all three EUS‐guided cystogastrostomy procedures using the wet simulation model and in all four EUS‐guided gastroenterostomy and gallbladder drainage procedures in the animal model. In the 3 weeks following the procedure, eating behavior was normal in all animals and there were no adverse events. The stents remained patent during this time and were removed without difficulty. The fistula was mature in all cases and a standard upper gastrointestinal endoscope was easily advanced via the fistula to observe the afferent and efferent loops or the lumen of the gallbladder. Necropsy confirmed complete adhesion between the stomach and the wall of the jejunum or gallbladder. Conclusions: Our study findings demonstrate the feasibility of this new LAMS system and its potential clinical value for interventional EUS. Abstract : Recently, a lumen‐apposing metal stent with less lumen‐apposing force was developed for use with a physician‐controlled electrocautery‐enhanced delivery system. In a wet simulation model and an animal model, Mukai and colleagues demonstrated the feasibility of this new lumen‐apposing metal stent system and its potential clinical value for interventional endoscopic ultrasound.